Formation of zoned ankerite in gravity-flow sandstones in the Linnan Sag, Bohai Bay Basin, eastern China: Evidence of episodic fluid flow revealed from in-situ trace elemental analysis. (March 2020) - Yang, Tian; Cao, Yingchang; Liu, Keyu; Tian, Jinchuan; Friis, Henrik; Zhou, Lingli
Abstract: It has been shown that ankerite in clastic reservoirs can preserve an extended record of diagenesis and thus the fluid flow history in sedimentary basins. Ankerite cements with distinct zoning textures are well developed in gravity-flow sandstones associated with magmatic intrusions in the Linnan Sag, Eastern China. This example offering a rare opportunity to investigate the history of complex diagenetic fluid flow events in a lacustrine rift basin. An integrated study including thin section petrography, fluid inclusion micro-thermometry, carbon and oxygen isotope, SEM-EDS, XRD, CL, BSE-EPMA, LA-ICP-MS analyses was undertaken. The aim is to resolve the mineralogical, geochemical and isotopic composition of the sandstone and constitutional minerals. The sandstones are mainly of lithic arkoses (Q43 F34 L23 ), with an average carbonate cements of approximately 8.2 wt %. The carbonate cements are dominated by zoned ankerite appearing as rhombohedral and poikilotopic blocky crystals. Calcite, ferroan calcite, dolomite and siderite cements are also present. Non-carbonate cements including barite, authigenic clay minerals, and quartz overgrowth are common in the sandstone. The δ 13  C values of ferroan calcite range from −4.2‰ to +1.2‰ PDB. Ferroan calcite was re-precipitated at a temperature of 93.1 °C at the expense of the dissolution of eodiagenesis carbonate cement in the sandstone. Ankerite was precipitated at temperature ranges from 107.8 to 140.9 °C, accompanied with the formation of pore-filling barite. The δ 13 C values of ankerite range from −1.8‰ to +1.1‰, and δ 18 O values range from −14.8‰ to −10.5‰, indicating an involvement of hydrothermal fluids in the formation of the zoned ankerite. The hydrothermal fluids were probably related to the mafic magmatic activities and migrated into the sandstones along faults. These fluids are rich in iron and magnesium, and also contains abundant inorganic carbon dioxide and sulphate, episodic charging into the reservoir. The abundances of most of the elements, including magnesium, iron, REEs and trace elements in the zoned ankerite consistently decrease away from the magma intrusion centres. We therefore conclude that multiple magmatic activities were primarily responsible for the zoned ankerite precipitation in the research area. The intimate relationship between magmatic activity and carbonate cementation in sandstone reservoirs documented in this paper may have significant implications for studying fluid flow in lacustrine rift basins. Highlights: Carbonate cements are dominated by zoned aankerite exhibit as rhombohedral and poikilotopic blocky crystals. Geochemical data induced the origin of a zoned ankerite effect of hydrothermal fluid. The multiple period of magma extrusion and the associated hydrothermal fluid flow is the main reason for zoned ankerite precipitation.